Bigger, faster, stronger - Shepard, Greg, 1942- 4 0 16; 5 (Champaign, IL : Human Kinetics, 2009)
Presents a training system to help high school and college athletes gain strength, flexibility, stamina, and agility, with photographs that illustrate form and technique.
Pt. I: The total program. Unified approach to training -- BFS rotational set-rep system -- BFS in-season training -- BFS readiness program -- Pt. 2: Strength exercises. Six absolutes of perfect technique -- Parallel squat and squat variations -- Power clean and quick lifts -- Hex-bar deadlift and deadlift variations -- Bench press and bench press variations -- Sport-specific auxiliary lifts -- Pt. 3: Speed, agility, and flexibility. Agility and the BFS dot drill -- Five-phase plyometric program -- Speed training -- BFS 1-2-3-4 flexibility program -- Pt. 4: Program administration. Organization and weight-room design -- Safety and liability -- BFS nutritional plan -- Be an eleven -- Why steroids don't work.
Includes index.
Adult;Adult
Keywords: 2 -- 0; 6; Training of.;Study and teaching (Secondary);Training.;Study and teaching. -- High school athletes;School sports.;Physical education and training;High school athletes;School sports.;Physical education; 20; 2